Driven to distraction : recognizing and coping with attention deficit disorder from childhood through adulthood - Hallowell, Edward M.; Ratey, John J., 1948- (New York : Anchor Books, 2011)
"Through vivid stories and case histories of patients--both adults and children ... [the authors] explore the varied forms ADHD takes, from hyperactivity to daydreaming. They dispel common myths, offer practical coping tools, and give a thorough accounting of all treatment options as well as tips for helping a diagnosed child, partner, or family member. But most importantly, they focus on the positives that can come with this 'disorder'--including high energy, intuitiveness, creativity, and enthusiasm"--P. [4] of cover.
What is Attention Deficit Disorder? -- "I sang in my chains like the sea" : the child with ADD -- "Sequence ravelled out of sound" : adult ADD -- Living and loving with ADD : ADD in couples -- The big struggle : ADD and the family -- Parts of the elephant : subtypes of ADD -- How do I know if I have it? : the steps toward diagnosis -- What can you do about it? : the treatment of ADD -- A local habitation and a name : the biology of ADD -- Appendix : where to find help.
"Originally published in hardcover in slightly different form by Pantheon Books ... in 1994, and subsequently published in paperback by Touchstone ... in 1995"--T.p. verso.
"Now revised and updated" -- Cover.
Includes bibliographical references (p. 363-366) and index.
Keywords: Attention-deficit disorder in adults -- Popular works; Attention-deficit hyperactivity disorder -- Popular works